Pathogenesis of septic shock in Pseudomonas aeruginosa pneumonia - Kurahashi, Kiyoyasu (American Society for Clinical Investigation, 1999)
The pathogenesis of septic shock occurring after Pseudomonas aeruginosa pneumonia was studied in a rabbit model. The airspace instillation of the cytotoxic P. aeruginosa strain PA103 into the rabbit caused a consistent alveolar epithelial injury, progressive bacteremia, and septic shock. The lung instillation of a noncytotoxic, isogenic mutant strain (PA103ΔUT), which is defective for production of type III secreted toxins, did not cause either systemic inflammatory response or septic shock, despite a potent inflammatory response in the lung. The intravenous injection of PA103 did not cause shock or an increase in TNF-α, despite the fact that the animals were bacteremic. The systemic administration of either anti–TNF-α serum or recombinant human IL-10 improved both septic shock and bacteremia in the animals that were instilled with PA103. Radiolabeled TNF-α instilled in the lung significantly leaked into the circulation only in the presence of alveolar epithelial injury. We conclude that injury to the alveolar epithelium allows the release of proinflammatory mediators into the circulation that are primarily responsible for septic shock. Our results demonstrate the importance of compartmentalization of inflammatory mediators in the lung, and the crucial role of bacterial cytotoxins in causing alveolar epithelial damage in the pathogenesis of acute septic shock in P. aeruginosa pneumonia.